Corporate Sports Activity and Work Morale: Evidence from a Japanese Automobile Maker - Masaru Sasaki; Fumio Ohtake (Institute for the Study of Labor (IZA), 2013)
This paper estimates the factors affecting the relationship between the wins and losses of corporate sports club teams and the work morale of employees, using an original survey of employees from a selected Japanese automobile maker. We find that corporate sports club teams' performance is an important factor influencing the work morale of older employees and employees who work with colleagues belonging to those teams in the same division. We can say statistically that the impacts of teams' wins and losses on changes in work morale of older employees at the individual level are symmetric; that is, the work morale of employees is significantly raised by own teams' wins but reduced by own teams' losses.
Keywords: L62; M52; M54; 330; work morale; corporate sports; subjective well-being analysis; Japan